The Effect of Insulating Oil Conditions in Transformer Bushing on Dielectric Response Analysis - Chanatip Srisub; Noppadol Maneerat; Warisanan Rojanasunan; Techatat Buranaaudsawakul; Pittaya Pannil; Norasage Pattanadech (My University, 2024)
The bushing is one of the important parts of a transformer. Once the transformer is operated; each transformer part including its bushing starts the degradation mechanism. In some cases, the dielectric strength degradation of the bushing can lead to severe consequences. Thus, the study and diagnosis of the bushing conditions are important. This study aims to investigate the characteristics of the oil-impregnated pressboard bushing under various oil conditions by filling the new mineral oil with a controlled moisture content and letting it reach an equilibrium state to examine the dielectric response of such bushing. To determine the dielectric characteristics of the investigated bushing, A Frequency Domain Spectroscopy (FDS) device was utilized. In the experiment, the dissipation factor, capacitance, and current measurement of the bushing with different water content level were measured. The bushing test object was tested with the frequency range of 1 mHz –1 kHz. The effect of moisture clearly influenced the low-frequency ranges of the FDS. The result will be discussed in the paper.
Keywords: Power Transformer Diagnostics and Insulation; High voltage insulation and dielectric phenomena; Non-Destructive Testing Techniques